Has government aging governance alleviated rural multidimensional relative poverty? Evidence from the China Rural Revitalization Survey - Wang, Heng; Yang, Shu; Zeng, Xianfeng; Wang, Yu (Frontiers in Public Health, 2025)
BackgroundPopulation aging poses a significant global challenge, particularly in rural areas where it increases economic burdens and living pressures, potentially pushing families into poverty.MethodsThis study utilizes data from the 2020 and 2022 China Rural Revitalization Survey (CRRS) and applies the Alkire-Foster (A-F) method to measure rural multidimensional relative poverty. A fixed effects model is used to systematically examine the mechanisms and impacts of government aging governance on rural multidimensional relative poverty.ResultsThe analysis yields three key findings: (1) Government efforts in aging governance have played a significant role in alleviating rural multidimensional relative poverty, through improvements in grassroots democratic quality and network conditions. (2) Rural households in China’s eastern regions benefit more from aging governance due to more developed infrastructure and broader social services. (3) The impact of aging governance on reducing multidimensional relative poverty is more pronounced in younger households compared to older adult households.ConclusionThis study underscores the role of government aging governance in addressing rural poverty and provides policy recommendations to develop a localized multidimensional relative poverty assessment system, improve governance capacity in aging-related affairs, and enhance grassroots democratic quality and rural digital infrastructure.